2021
DOI: 10.1038/s41598-021-00730-8
|View full text |Cite|
|
Sign up to set email alerts
|

Unveiling microbial preservation under hyperacidic and oxidizing conditions in the Oligocene Rio Tinto deposit

Abstract: The preservation of biosignatures on Mars is largely associated with extensive deposits of clays formed under mild early Noachian conditions (> 3.9 Ga). They were followed by widespread precipitation of acidic sulfates considered adverse for biomolecule preservation. In this paper, an exhaustive mass spectrometry investigation of ferric subsurface materials in the Rio Tinto gossan deposit (~ 25 Ma) provides evidence of well-preserved molecular biosignatures under oxidative and acidic conditions. Time of fli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 110 publications
0
13
0
Order By: Relevance
“…Both the reduction and oxidation of Fe could act as different paths to dissolve minerals and further increase the content of soluble metals in the underwater reservoir. Fe 3+ can react with the S 2− of the pyrite (FeS 2 ) oxidizing it to SO 4 2− while Fe 3+ is reduced to Fe 2+ and protons are released as well [93,94]. The Fe 2+ would be oxidized indirectly through the NDFO by Shewanella sp.…”
Section: Iron Oxidation and Reduction Assaysmentioning
confidence: 99%
“…Both the reduction and oxidation of Fe could act as different paths to dissolve minerals and further increase the content of soluble metals in the underwater reservoir. Fe 3+ can react with the S 2− of the pyrite (FeS 2 ) oxidizing it to SO 4 2− while Fe 3+ is reduced to Fe 2+ and protons are released as well [93,94]. The Fe 2+ would be oxidized indirectly through the NDFO by Shewanella sp.…”
Section: Iron Oxidation and Reduction Assaysmentioning
confidence: 99%
“…The distribution of inorganic and organic ions was performed to understand the association among the inorganic and organic compounds with the different elements of the structure and texture sample. In sample 95E5/3, the ion distribution characterized by the ToF-SIMS mapping capability greatly depends on the arrangement of the rock’s primary components like skeletal/non-skeletal grains and bioclasts, and the mineral matrix or cement [ 34 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polished sections for sample 95E5/3 were prepared for mineral and textural analysis under a microscope and molecular surface analysis by ToF-SIMS [ 34 ]. The surface sample was extra-polished using a 0.3 mm alumina paste to reduce surface imperfections that produce frequent interferences during the surface analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Rio Tinto, an exhaustive SIMS investigation demonstrated that molecular biosignatures could be well preserved under the acidic oxidative surface of Rio Tinto (Fernández-Remolar et al, 2021). Organic materials as biosignatures in Rio Tinto were isolated from inorganic substances and detected using EA-IRMS (Table 2).…”
Section: Applications Of Instrumentsmentioning
confidence: 99%